2019
DOI: 10.3390/su11236619
|View full text |Cite
|
Sign up to set email alerts
|

Crop Vulnerability to Weather and Climate Risk: Analysis of Interacting Systems and Adaptation Efficacy for Sustainable Crop Production

Abstract: Climate change is increasing mean and extreme temperatures in the Southwestern United States, leading to a suite of changes affecting agricultural production. These include changes in water, soils, pathogens, weeds, and pests comprising the production environment. The aim of this synthesis is to describe the anticipated leading agricultural pressures and adaptive responses, many of which are near-term actions with longer-term consequences. In the semiarid Southwestern United States, climate change is expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 136 publications
(146 reference statements)
0
21
0
1
Order By: Relevance
“…Los resultados de la presente investigación señalan a los factores ambientales y climáticos como los más riesgosos dentro de un sistema agrícola en concordancia con las afirmaciones de otras investigaciones (Elias et al, 2019;Pelka et al, 2015), principalmente porque algunos eventos específicos de este tipo son impredecibles y el tiempo de reacción es reducido, siendo el factor donde más acciones y planeación deben tomar los productores, así como la cantidad de recursos financieros que deben destinar para enfrentar estos riesgos.…”
Section: Discussionunclassified
“…Los resultados de la presente investigación señalan a los factores ambientales y climáticos como los más riesgosos dentro de un sistema agrícola en concordancia con las afirmaciones de otras investigaciones (Elias et al, 2019;Pelka et al, 2015), principalmente porque algunos eventos específicos de este tipo son impredecibles y el tiempo de reacción es reducido, siendo el factor donde más acciones y planeación deben tomar los productores, así como la cantidad de recursos financieros que deben destinar para enfrentar estos riesgos.…”
Section: Discussionunclassified
“…1.1.1. Research on the Effect of Climate on Agricultural Production Elias et al [1] studied the changes in agricultural production caused by extreme temperature in the southwest of the United States, and described the agricultural pressure and adaptive response of the United States by analyzing the changes in variable elements. The results showed that the water shortage in the semi-arid areas of the southwest of the United States was becoming more and more serious, resulting in the reduction of crop production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some progress is still needed to gain the practical advantages of nanotechnology, such as better design of processes, risk assessment of nanopesticides and nanofertilizers, and regulations for commercialization of nanoagroproducts (Chen and Yada, 2011;de Oliveira et al, 2014;Amenta et al, 2015). Another challenging issue yet to be resolved includes farming systems to deal better with unpredictable climate variability, including new varieties of crops that can sustain drought, heat, and other environmental stress to convey the whole spectrum of modern farming practices worldwide (Elias et al, 2019). We strongly believe that a broad perspective of nanotechnology is essential to fulfilling the goal of helping foster global agriculture.…”
Section: Introductionmentioning
confidence: 99%